Shotgun proteomics approach for the establishment of peptide markers for pork - Mohd Yusoff, Mohd Hafis Yuswan (2018)
Statistically, in 2015 the largest population in the world is the Christians, nevertheless, by 2060 the population of Muslim is expected to be nearly equal to the Christians. This indicates that the halal status of any particular food as a future global concern. According to the Food and Agricultural Organisation of the United Nations 2009, the demand for meat is expected to increase drastically for the developing countries, from 26 to 37 kg of average annual per capita consumption from the year 2000 to 2030. Consequently, certain manufacturers have unethically adulterated the meat owing to the desire to generate a high-profit margin as well as to fulfil the market demand, whereby pork is added to beef. These consequences highlight a requirement for meat authentication analysis. Recently, qPCR is the most famous genomic-based method that has been employed in the routine laboratories worldwide; owing to the lower limit of detection method as compared to any other proteomic-based methods such as SDS-PAGE and ELISA. In contrast to the DNA, the peptide sequences are extremely stable, in which their intactness remain against chemical or mechanical processes. The objective of this study, therefore, is to establish the peptide markers for pork by a newly shotgun proteomics approach, which those peptide markers shall be related to the contractile proteins of meat such as myosin, actin, tropomyosin, or troponin complexes. Initially, the peptide masses of proteolytic peptides, generated from peptide mass fingerprinting of LC-MS analysis, were analysed by principal component analysis (PCA) to overview the distribution pattern of 577 peptide masses among pork, beef, and broiler. Then, the most significant peptide masses for pork were determined from a validated PCA model through a discriminant analysis of orthogonal partial least square. Consequently, only seven potential peptide markers for pork were identified, but only five peptide markers were true-positive, as confirmed by another independent tandem LC-MS/MS analysis. Subsequently, the MS/MS spectra of true-positive peptide markers were annotated for their peptide sequences and inferential proteins through de novo database search engine (MS-Taq tool of ProteinProspector 5.20.0). Furthermore, a validation study was conducted to measure the precision, detection limit, and specificity of the peptide markers in relation to their reliability and applicability. In summary, only three reliable and applicable peptide markers from contractile proteins of pork had successfully established through an advanced shotgun proteomics approach by using Agilent 1200 Series high-performance liquid chromatography hyphenated with AB Sciex 4000 QTrap mass spectrometer with a detection limit was 10% of pork. Unfortunately, the three peptide markers are not applicable to processed pork. This finding might be owing to a modification of certain amino acid in the peptide marker sequence through deamination or oxidation due to the extreme processing. Therefore, further comprehensive study is warranted for processed pork, as the established peptide markers from this study were successfully developed for raw pork not processed pork. Moreover, an advanced method validation for individual peptide marker is required, before it can be routinely implemented in the laboratory as a standard procedure for meat authentication.